Mechanical behavior and wear prediction of stir cast Al–TiB2 composites using response surface methodology - Suresh, S.; Shenbaga Vinayaga Moorthi, N.; Vettivel, S.C.; Selvakumar, N. (Materials in engineering, 2014)
•Various experiments were conducted on Al6061–TiB2 composite.•XRD and EDS studies confirm the crystalline size and elements present.•SEM, EDS and OM observations were used to study the characteristics.•Curve fitting and RSM design methods are effectively used to develop the model. Al6061 was reinforced with various percentages of TiB2 particles by using high energy stir casting method. The characterization was performed through X-ray Diffraction, Energy Dispersive Spectrum and Scanning Electron Microscope. The mechanical behaviors such as hardness, tensile strength and tribological behavior were investigated. Wear experiments were conducted by using a pin-on-disc wear tester at varying load. The curve fitting technique was used to develop the respective polynomial and power law equations. The wear mechanism of the specimen was studied through SEM. Response Surface Methodology was used to minimize the number of experimental conditions and develop the mathematical models between the key process parameters namely weight percentage of TiB2, load and sliding distance. Analysis of Variance technique was applied to check the validity of the developed model. The mathematical model developed for the specific wear rate was predicted at 99.5% confidence level and some useful conclusions were made.